Teaching Young Readers to Navigate a Digital Story When Rules Keep Changing. (May 2014) - Javorsky, Kristin; Trainin, Guy
Abstract As mobile technologies such as tablets and smartphones offer opportunities to view stories in digital format, young readers are faced with new challenges in the reading task. The authors conducted an exploratory study of digital story applications on a mobile reading device and found that digital story applications are capable of taking large departures from paper‐based text in both features and conventions, and moreover, that these differences are currently presented to readers in multiple, sometimes unpredictable ways. We propose that the existence of this variability itself is a key concept that young readers of digital texts must acquire, and suggest several practical strategies for use in the classroom to foster this understanding.